ПИТАННЯ СТАТЕВОГО ВИХОВАННЯ МОЛОДІ ДОНЕЦЬКОГО РЕГІОНУ (World Science, 2019)
Sex education is an integral part of the overall school and family upbringing process. One of the main tasks of modern domestic educational institutions is properly organized education in the sexual sphere. The goal of sexual education and preparation for family life should be the prevention and correction of major sexual behavior. The article presents the survey results on the issues of sexual education of young people in Donetsk region at the present stage. Problematic issues were identified regarding sexual education, contraception, family planning and obtaining information about sexually transmitted diseases based on an anonymous survey conducted by medical university students. The main directions of educational work concerning these issues are identified.